PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAPKOMITMEN ORGANISASI DAN KEPUASAN KERJA PEGAWAI PADA KANTOR DESA DI KECAMATAN KALIKOTES KABUPATEN KLATEN - ENDANG SETYOWATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2023)
This research aims to determine the extent to which the influence of leadership and the work environment on performance through organizational commitment and job satisfaction of employees at the Village Office in Kalikotes District, Klaten Regency, Central Java. The data we use in this research is primary data. The number of samples is 45 employees who work at the Village Office in Kalikotes District, Klate Regency. The sampling technique in this research uses the census method. The data in this research were obtained directly from the results of distributing questionnaires. This research analysis tool uses path analysis. The results of the t test show that the leadership variable has no significant effect on the organizational commitment variable. Job satisfaction variable has a significant effect on organizational commitment variable. Leadership variable has a significant effect on job satisfaction variable. Work environment variables have a significant effect on job satisfaction variables. Leadership has a significant effect on employee performance. Work environment variables have a significant effect on employee performance. Variable Employee organizational commitment has a significant effect on employee performance. Job satisfaction variable has a significant effect on employee performance. The results of the F test show that simultaneously leadership variables, work environment variables, organizational commitment variables and employee job satisfaction variables have a positive and significant effect on employee performance. R2 totals 98.4%. This means that employee performance is explained by leadership, work environment, organizational commitment and employee job satisfaction by 98.4% and the remaining 1.6% is explained by other variables outside the research model such as compensation. The conclusion from this path analysis shows that the use of intervening variables is not effective. The work environment is the most effective in improving employee performance, because it has the most positive and very significant influence.